Dragonsblood - McCaffrey, Todd (New York : Ballantine Books, 2006)
With the dragons of Pern dying and the only person who can save them long dead, the grieving dragon riders find clues in the lyrics of an ancient ballad to long forgotten knowledge and secrets hidden somewhere in Benden Weyr.
99037
Keywords: Pern (Imaginary place); Life on other planets; Dragons; Science fiction; Science fiction